Chronic Myeloid Leukemia in 2020 - Hehlmann, Rüdiger (HemaSphere, 2020)
New insights have emerged from maturing long-term academic and commercial clinical trials regarding optimum management of chronic myeloid leukemia (CML). Velocity of response has unexpectedly proved less important than hitherto thought, does not predict survival, and is of unclear relevance for treatment-free remission (TFR). Serious and cumulative toxicity has been observed with tyrosine kinase inhibitors that had been expected to replace imatinib. Generic imatinib has become cost-effective first-line treatment in chronic phase despite chronic low-grade side-effects in many patients. Earlier recognition of end-phase by genetic assessment might improve prospects for blast crisis (BC). TFR has become an important new treatment goal of CML. To reflect this new situation ELN has recently revised and updated its recommendations for treating CML. After a brief review of 175 years of CML history this review will focus on recent developments and on current evidence for treating CML in 2020.
Gesehen am 06.06.2020